Promoting self-determination in students with severe intellectual disability - Jon Efendi (Indonesian Institute for Counseling, Education and Theraphy, 2021)
Outreach counseling is a program of guidance and counseling to maximize service as an alternative when the counseling process is generally difficult to do. Students with intellectual disability is a different communities as the basis for the implementation of the guidance in the community. Outreach guidance need to touch various efforts in helping the students with intellectual disability in order to grow optimally, and able to cope with the problem of self-determination. The supervisor does not need to involve themselves directly in handling guidance students with intellectual disability namely by empowering the students' environment.